Assessment, didactics, and architecture education: a hermeneutics experience - Ocampo Hurtado, Juan Gabriel (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Architecture in the contemporary world has been vigorously debated concerning its sense and application from the educational field, in which induction as a tradition faces the cognitive approach in search of the improvement of curriculum. Architecture as an expression of human existence is thought of as a phenomenon susceptible to be felt, perceived, and analyzed making use of students’ inference. On this basis, it is argued the importance of assessing what has been learnt and valuing what has not. Hermeneutics as a way of interpretation was offered to students that participated in this research in order to try out Max Van Manen’s methodological proposal, known as hermeneutical phenomenology. As a part of the results, a methodology applicable to the learning of architecture is proposed.